2015
DOI: 10.1016/j.fsi.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of phenoloxidase and superoxide dismutase in the manila clam Venerupis philippinarum challenged with Vibrio tapetis – Part I: Spatio-temporal evolution of enzymes' activities post-infection

Abstract: Manila clams, Venerupis philippinarum (Adams and Reeve, 1850), were experimentally challenged with two Vibrio tapetis strains: CECT4600T, the causative agent of Brown Ring Disease (BRD); and LP2 supposedly non-pathogenic in V. philippinarum. Changes in phenoloxidase (PO) and superoxide dismutase (SOD), two major enzymes involved in immunity, were studied in two tissues, the mantle and hemolymph for 30 days after infection in the extrapallial cavity. Bacterial infection in V. philippinarum resulted in modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
(82 reference statements)
0
17
0
1
Order By: Relevance
“…These results imply an effect of injection on animals which were supposedly infected by V. tapetis , present in their environment before sampling, despite the quarantine stage. It has already been shown that injection or handling could stimulate bacterial proliferation ( Le Bris et al, 2015 ; Jean et al, in press ). Focusing on non-injected clams, i.e., at 0d for V. tapetis - and FSW-injected clams and all the sampling times for non-injected clams, the interpretation that V. tapetis was present in individuals before sampling is corroborated: 3 individuals among 36 were already carrying bacteria on the day of injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply an effect of injection on animals which were supposedly infected by V. tapetis , present in their environment before sampling, despite the quarantine stage. It has already been shown that injection or handling could stimulate bacterial proliferation ( Le Bris et al, 2015 ; Jean et al, in press ). Focusing on non-injected clams, i.e., at 0d for V. tapetis - and FSW-injected clams and all the sampling times for non-injected clams, the interpretation that V. tapetis was present in individuals before sampling is corroborated: 3 individuals among 36 were already carrying bacteria on the day of injection.…”
Section: Discussionmentioning
confidence: 99%
“…In order to accurately inoculate CECT4600 T at the target dilution of 10 7 cells/mL during the experiment, enumeration of bacteria was performed to measure the absorbance at 492 nm on a Multiskan spectrophotometer (Fisher Scientific, Hampton, NH, USA). Vibrio tapetis culture density was calculated according to the formula 1.3 10 9 × DO − 3.6 10 7 CFU/mL ( Choquet, 2004 ; Le Bris et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, LPO is indicative of the damage caused by reactive oxygen species (ROS) to cell membrane lipids, and it is useful for assessing exposure to, and the effects of pollutants in mussels (Campillo et al, 2013;Cheung et al, 2001;ICES, 2013;Regoli and Principato, 1995;Regoli, 1998). POs are enzymes involved in humoral immune defenses and are key enzymes of melanization (Luna-Acosta et al, 2011;Le Bris et al, 2014) which is the major innate defense system in invertebrates, during which highly reactive and toxic quinine intermediates are produced to form melanin by polymerization (Cerenius and Soderhall, 2004). Regarding physiological biomarkers, the measurement of the scope for growth (SFG) has also been used as a measure of stress effects caused by pollutants in marine organisms (Albentosa et al, 2012a;Bellas et al, 2014;Halldörson et al, 2005;Widdows et al, 2002Widdows et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The molluscs performed humoral and cellular immune reactions in dealing with pathogens and stress responses [1,2]. In immune reactions, pattern recognition proteins such as the galectins are involved in the recognition of pathogen-associated molecular patterns of microorganisms [3].…”
Section: Introductionmentioning
confidence: 99%